Infrared-Induced Rotamerization of Oxalic Acid Monomer in Argon Matrix - Maçôas, Ermelinda M. S. (2000)
Infrared-induced conformational isomerization of oxalic acid monomer isolated in an argon matrix at 7.5 K was studied by infrared spectroscopy. For the first time, three conformational states of this molecule were identified experimentally and their vibrational spectra are assigned. In good agreement with density functional theory predictions, all the observed conformers exhibit a trans OC−CO axis, differing in the relative conformation of their O−C−O−H axes. In the most stable conformer (belonging to the C2h symmetry point group), two intramolecular OH···O hydrogen bonds are present. The second (Cs) most stable conformer shows a single OH···O bond, and the third one (C2h) does not exhibit any intramolecular hydrogen bond. Using narrowband tunable irradiation in the near-infrared region it was possible to promote very efficiently conformer interconversions, which was followed spectroscopically.